2019
DOI: 10.1088/1361-6463/ab2faf
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial traps and mobile ions induced flatband voltage instability in 4H-SiC MOS capacitors under bias temperature stress

Abstract: Bias temperature stresses (BTSs) are critical factors that cause severe threshold voltage (V th ) instability in silicon carbide (SiC) metal-oxide-semiconductor (MOS) devices. In this work, we studied the behavior of flatband voltage (V fb ) instability in 4H-SiC MOS capacitors under various BTSs from low temperature (LT) to high temperature (HT) considering the combined effects of interfacial traps and mobile ions. Results showed that nitrogen and nitrogen-hydrogen plasma passivation improved the V fb instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…First, many interface traps and NIOTs can be occupied by electrons due to the decrease in the difference between E f and E c , resulting from the decrease in test temperature. [9,34] Second, a low temperature can reduce the de-trapping rate of trapped carriers. [9,35] Therefore, the electrical signals of many traps can be tested by C-V curves.…”
Section: The V Fb Stability Under Btsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, many interface traps and NIOTs can be occupied by electrons due to the decrease in the difference between E f and E c , resulting from the decrease in test temperature. [9,34] Second, a low temperature can reduce the de-trapping rate of trapped carriers. [9,35] Therefore, the electrical signals of many traps can be tested by C-V curves.…”
Section: The V Fb Stability Under Btsmentioning
confidence: 99%
“…[9,34] Second, a low temperature can reduce the de-trapping rate of trapped carriers. [9,35] Therefore, the electrical signals of many traps can be tested by C-V curves. We observed that ∆V fb decreases with the increase in O 3 oxidation temperature, indicating that V fb BTI can be effectively improved by O 3 oxidation at high temperatures.…”
Section: The V Fb Stability Under Btsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the voltage increases, the window of the curve will gradually become smaller and then turn into a normal counterclockwise hysteresis curve. This is due to the carrier injection from the top electrode into the defect state of the SiN x layer [ 30 , 31 ]. A thicker SiN x control layer can block the transfer of carriers between the top electrode and the nc-Si dots, thereby improving the carrier injection efficiency from the Si substrate to the nc-Si dots.…”
Section: Introductionmentioning
confidence: 99%